Principles of Adult Surgical Critical Care - Martin, Niels D.; Kaplan, Lewis J. (Springer International Publishing : Imprint: Springer, 2016)
This text provides a high level, comprehensive but concise review of adult surgical critical care. It can be used to review complex topics of critical illness in surgical patients, as a reference tool, or as preparation for a board examination. It is focused on the surgical patient including high yield facts, evidence-based guidelines, and critical care principles. To remain succinct, it concentrates on surgically relevant care. Further, the text is written with an expectation that reader already possesses a basic understanding of critical care pathophysiology and clinical practices such as those acquired during residency. Organized by organ system, each section contains several chapters addressing relevant disorders, monitoring and treatment modalities, and outcomes. Principles of Adult Surgical Critical Care will be of use to intensivists caring for surgical patients regardless of parent training domain. Additionally, this work is intended to be used by surgical critical care fellowship trainees as well as other advanced practice providers such as nurse practitioners and physician assistants who provide care in ICUs and emergency departments alike. .